Preparation method of flexible P (VDF-TrFE) / BaTiO3 piezoelectric composite film with layer-by-layer interlocking structure

By generating a BaTiO3 layer in situ on the titanium foil substrate and combining it with P (VDF-TrFE) to form a piezoelectric composite film with a layer-by-layer interlocking structure, the shortcomings in durability and piezoelectric properties of the existing piezoelectric composite film are solved, and high-performance piezoelectric characteristics and deformation capabilities are achieved.

CN119768028AActive Publication Date: 2025-04-04SHANGHAI JIAOTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411881353.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-04
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing piezoelectric composite films have problems of low durability and poor piezoelectric performance in applications, and are difficult to meet the needs of energy collection and sensing.

Method used

A flexible titanium foil substrate is used to generate a BaTiO3 piezoelectric layer in situ, and the piezoelectric performance of the film is improved by impregnating the P(VDF-TrFE) solution. The interlocking method of two piezoelectric structures with a naturally transformed three-dimensional particle network structure is used to form a P(VDF-TrFE)/BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure.

Benefits of technology

It realizes a high-performance piezoelectric composite film, which has excellent piezoelectric characteristics and deformation capabilities, breaks through the requirements of traditional materials for uniform dispersion of substrates and fillers, and is suitable for energy collection, piezoelectric sensors, and catalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768028A_ABST
    Figure CN119768028A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a flexible P (VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure, and the preparation method comprises the following steps: S1, carrying out electrochemical anodic oxidation on a titanium foil in an organic electrolyte, and generating a TiO2 layer on the surface in situ; s2, putting the titanium foil treated in the step S1 into a barium-containing solution, carrying out hydrothermal reaction, and generating a BaTiO3 layer on the surface in situ; s3, coating the surface of the BaTiO3 layer with a P (VDF-TrFE) solution, and carrying out annealing treatment to form a flexible P (VDF-TrFE) / BaTiO3 composite film; and S4, carrying out electric polarization treatment on the flexible P (VDF-TrFE) / BaTiO3 composite thin film to obtain the flexible P (VDF-TrFE) / BaTiO3 composite thin film The piezoelectric composite film with a layer-by-layer interlocking structure prepared by the method has excellent piezoelectric property and deformability, and can be used in the fields of energy collection, piezoelectric sensors, piezoelectric catalysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric film preparation, and in particular to a method for preparing a flexible P (VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure. Background Art

[0002] As a traditional functional material, piezoelectric materials can realize the conversion between mechanical energy and electrical energy due to the special non-central symmetry of their crystal structure. They are widely used in the fields of electronic information, energy industry, catalytic medicine, etc. Among them, piezoelectric films are widely used in intelligent application scenarios such as energy collection, sensors, and flexible electronics due to their advantages such as small size, light weight, high frequency response, and wide bandwidth. The brittleness of common piezoelectric ceramics such as lead zirconate titanate, lead magnesium niobate, and barium titanate seriously limits the application scenarios of films; piezoelectric polymers with good deformation ability such as polytetrafluoroethylene and its copolymers are limited in energy conversion and sensing due to their low piezoelectric coefficient. Therefore, a thin film material with both flexibility and excellent piezoelectric properties has become an urgent need. Piezoelectric composite film is a material that combines piezoelectric ceramics and polymers to give full play to the advantages of both. Filling the piezoelectric ceramic reinforcement phase into the polymer matrix can improve the piezoelectric properties of the material to a certain extent and retain the flexibility of the polymer system. However, with the expansion of the scope of application, piezoelectric films still have some problems in practical applications. First, the piezoelectric composite film lacks a support for coordinated deformation and exhibits low durability. Second, although the piezoelectric performance of the piezoelectric composite film is improved compared with that of pure piezoelectric polymer materials, it is still difficult to meet people's needs for energy collection, sensing, etc. compared with the performance of bulk piezoelectric materials.

[0003] Patent CN110690342A discloses a flexible piezoelectric energy conversion device based on carbon-coated barium titanate / PVDF. By uniformly mixing polyvinylidene fluoride with carbon-coated barium titanate nanoparticles, it can convert low-frequency mechanical energy into electrical energy to power wearable electronic devices, but its piezoelectric performance is poor and the piezoelectric film has defects. Patent CN104734563A discloses a method for preparing a flexible lead-free barium titanate piezoelectric generator, providing a flexible lead-free barium titanate piezoelectric generator that is easy to carry and can be self-powered and its preparation method, but the selected substrate reduces the overall flexibility of the piezoelectric generator.

[0004] Micro-arc oxidation is often used in the existing preparation methods of barium titanate piezoelectric coatings. This method uses a water solvent system as an electrolyte. The barium titanate content in the prepared micro-arc oxidation coating is low, and the barium titanate is dispersed in the micro-arc oxidation coating. The coating as a whole cannot show piezoelectric properties on a macroscopic level, and only shows a microscopic piezoelectric effect in the local microscopic area containing barium titanate crystals. In order to improve the piezoelectric properties of piezoelectric composite films, the structural design of composite materials has received extensive attention from researchers. The dispersion form and degree of the piezoelectric filling phase in the matrix material affect the piezoelectric properties of the material, but the destruction of the continuity of the piezoelectric particles by the dispersion of the material system causes discontinuous changes in the performance. Maintaining the continuity of the piezoelectric phase performance has become an important consideration for improving the piezoelectric performance of the material. However, simply increasing the interface bonding through horizontal interfaces or geometric structures often cannot optimize the performance of each piezoelectric phase. Therefore, there is an urgent need for a piezoelectric composite film with excellent piezoelectric particle continuity. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure. The present invention utilizes a flexible titanium foil substrate to in-situ generate a BaTiO3 piezoelectric layer, improves the piezoelectric properties of the BaTiO3 film by impregnating it with a P(VDF-TrFE) solution, and adopts an interlocking mode of two piezoelectric structures of a naturally transformed three-dimensional particle network structure. Under the condition of giving full play to the piezoelectric polarization transition, a high-performance P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure is obtained. The piezoelectric composite film has both excellent piezoelectric properties and deformation capabilities, and the inherent layer-by-layer interlocking structure breaks through the traditional requirements for the uniform dispersion of the matrix and the filler in the preparation of piezoelectric composite materials, and can be used in the fields of energy collection, piezoelectric sensors, and piezoelectric catalysis.

[0006] The purpose of the present invention can be achieved by the following scheme:

[0007] In a first aspect, the present invention provides a method for preparing a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film having a layer-by-layer interlocking structure, comprising the following steps:

[0008] S1. Electrochemically anodic oxidation is performed on titanium foil in an organic electrolyte to generate a TiO2 layer on the surface in situ; wherein the anode is titanium foil and the cathode is an inert conductive electrode;

[0009] S2, placing the titanium foil treated in step S1 into a barium-containing solution to perform a hydrothermal reaction to in-situ generate a BaTiO3 layer on the surface;

[0010] S3, coating the P(VDF-TrFE) solution on the surface of the BaTiO3 layer, and annealing to form a flexible P(VDF-TrFE) / BaTiO3 composite film;

[0011] S4. Performing an electric polarization treatment on the flexible P (VDF-TrFE) / BaTiO3 composite film to obtain the flexible P (VDF-TrFE) / BaTiO3 piezoelectric composite film.

[0012] As a technical solution of the present invention, in step S1, the titanium foil is a foil of pure titanium or titanium alloy, and has a thickness of 20 to 100 μm. Preferably, the thickness of the titanium foil is 20 to 50 μm.

[0013] As a technical solution of the present invention, in step S1, the titanium foil is a pretreated and cleaned titanium foil; the pretreatment step includes: using (PET) tape to seal the titanium foil on one side, ultrasonically cleaning the sealed titanium foil in acetone, ethanol and pure water for 5-10 minutes in turn, and drying with cold air.

[0014] In the present invention, the electrochemical anodization is carried out using a double-electrode system; after the anodization, the titanium foil is rinsed with deionized water and dried.

[0015] As a technical solution of the present invention, in step S1, the organic electrolyte comprises 0.01-0.3 mol / L ammonium fluoride and 0.1-3 mol / L ethylene glycol. Preferably, the organic electrolyte comprises 0.05-0.08 mol / L ammonium fluoride and 0.5-0.8 mol / L ethylene glycol.

[0016] As a technical solution of the present invention, in step S1, the parameters of the electrochemical anodization are set as follows: the water bath temperature is 20-30°C, the stirring speed is 5-25rpm, the DC power supply adopts a constant voltage mode, the voltage is 40-80V, and the treatment time is 30-90min. Preferably, the parameters of the electrochemical anodization are set as follows: the water bath temperature is 20-26°C, the stirring speed is 5-10rpm, the DC power supply adopts a constant voltage mode, the voltage is 55-70V, and the treatment time is 40-60min.

[0017] As a technical solution of the present invention, in step S1, the inert conductive electrode includes any one of a graphite electrode, a platinum electrode, and a pure titanium electrode. Preferably, the inert conductive electrode is a graphite electrode.

[0018] As a technical solution of the present invention, in step S2, the barium-containing solution includes an aqueous solution of barium hydroxide with a concentration of 1 to 2 mol / L. Preferably, the concentration of the barium-containing solution is 1.5 to 2 mol / L. In some embodiments, deionized water boiled for 10 to 30 minutes is used to dissolve Ba(OH)2·8H2O powder to prepare an aqueous solution of barium hydroxide.

[0019] As a technical solution of the present invention, in step S2, the temperature of the hydrothermal reaction is 180-220°C, and the reaction time is 1-5 days. If the hydrothermal reaction temperature is too low, the transformation rate and degree of transformation will be affected; if the hydrothermal reaction temperature is too high, the hydrothermal reactor will not be able to withstand it. Preferably, the reaction time of the hydrothermal reaction is 2-5 days.

[0020] In some embodiments, after the BaTiO3 layer is formed, the titanium foil is taken out and the surface is rinsed with a 5-20% by volume dilute acetic acid solution and deionized water for 5-10 minutes and dried. Preferably, the volume content of the dilute acetic acid solution is 5-10%.

[0021] As a technical solution of the present invention, in step S3, the concentration of the P(VDF-TrFE) solution is 0.5 to 3 g / L. Preferably, the concentration of the P(VDF-TrFE) solution is 0.5 to 1.0 g / L. In some embodiments, the P(VDF-TrFE) solution is obtained by dissolving polyvinylidene fluoride PVDF powder, and the solvent used includes any one of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), acetone (Acetone), and N-methylpyrrolidone (NMP).

[0022] As a technical solution of the present invention, in step S3, the annealing treatment is divided into two stages, the first stage is 60-80°C vacuum insulation for 1-4 hours, and the second stage is 120-140°C insulation for 6-12 hours. The first stage allows the organic solvent to fully volatilize, and the second stage allows P(VDF-TrFE) to fully crystallize.

[0023] As a technical solution of the present invention, in step S4, the parameters of the polarization treatment are set as follows: the distance between the needle tip and the sample surface is controlled to be between 5 and 20 mm, the high-voltage DC power supply is adjusted to display the voltage of 5 to 20 kV, and the polarization time is 30 to 90 min. Preferably, the parameters of the polarization treatment are set as follows: the distance between the needle tip and the sample surface is controlled to be between 5 and 10 mm, the high-voltage DC power supply is adjusted to display the voltage of 10 to 20 kV, and the polarization time is 30 to 60 min. The polarization treatment of the present invention adopts non-contact corona polarization treatment to excite the piezoelectric properties of the film.

[0024] In a second aspect, the present invention provides a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film having a layer-by-layer interlocking structure obtained by the preparation method.

[0025] Compared with the existing micro-arc oxidation method for preparing barium titanate layer, the micro-arc oxidation method uses a water-solvent electrolyte, and the prepared micro-arc oxidation coating (i.e., titanium dioxide layer) is a rough and porous ceramic oxide layer with irregular pore structure and micron-sized pores. The titanium dioxide in the coating contains crystalline and amorphous phases; the relative content of barium titanate crystals in the coating is low after hydrothermal treatment, and barium titanate has no transition region of structure and composition, and the barium titanate layer cannot form a layer-by-layer interlocking structure with PVDF. The present invention uses anodization with an organic solvent as an electrolyte, and the anodized titanium dioxide amorphous layer prepared by the present invention has a nanocolumn array structure, the nanopores are not interconnected and the size is uniformly distributed, and a coating with a gradually transitioned structure and composition is formed after hydrothermal treatment, which can form a layer-by-layer interlocking structure with PVDF, and has a significant effect on the improvement of the piezoelectric coefficient.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention generates a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure on the surface of titanium foil in situ by anodization and in-situ hydrothermal synthesis, thereby achieving superior piezoelectric performance output of the flexible composite film.

[0028] (2) The present invention regulates the phase content and crystallinity of BaTiO3 inside the film by optimizing the hydrothermal reaction process, providing a theoretical and technical basis for the design and preparation of high-voltage electrical composite films.

[0029] (3) The method of the present invention proposes the concept of a two-phase composite piezoelectric material with a layer-by-layer interlocking structure, fully coordinating the piezoelectric responses between different piezoelectric materials, and providing a novel approach for the preparation of piezoelectric composite materials.

[0030] (4) The method of the present invention is a new strategy for preparing piezoelectric composite films, which solves the problem of the incompatibility between the piezoelectric properties and flexibility of piezoelectric films, and the preparation process is simple, efficient and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0032] Figure 1 The cross-sectional SEM microstructure of the P(VDF-TrFE) / BaTiO3 film prepared in the example;

[0033] Figure 2is the piezoelectric coefficient d of the piezoelectric films prepared in Examples 1-5 and Comparative Examples 1-3 33 ;

[0034] Figure 3 is the hysteresis loop of P(VDF-TrFE) / BaTiO3 thin film sample;

[0035] Figure 4 Schematic diagram of device assembly and piezoelectric output curve for P(VDF-TrFE) / BaTiO3 thin film sample;

[0036] Figure 5 The typical surface morphology and cross-sectional micromorphology of the anodized coating of Example 1; wherein the left figure is the surface micromorphology of the anodized coating, and the right figure is the cross-sectional micromorphology of the anodized coating;

[0037] Figure 6 The typical surface morphology and cross-sectional micromorphology of the micro-arc oxidation coating of comparative example 3; wherein, the left figure is the surface micromorphology of the micro-arc oxidation coating, and the right figure is the cross-sectional micromorphology of the micro-arc oxidation coating. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0039] Example 1

[0040] This embodiment provides a method for in-situ generating a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure on a titanium foil surface, the steps are as follows:

[0041] (1) A TA1 titanium foil with a thickness of 50 μm was cut into square samples of 50 mm × 50 mm, sealed on one side with PET tape, and then ultrasonically cleaned in acetone, ethanol, and pure water for 10 min, respectively, and dried to obtain a pretreated titanium foil sample;

[0042] (2) The titanium foil sample treated in step (1) is immersed in an electrolyte containing 0.05 mol / L ammonium fluoride and 0.5 mol / L ethylene glycol, with a graphite electrode as the cathode and the titanium foil sample as the anode. A constant voltage DC power supply adopts a 60 V constant voltage output. The anodization treatment is carried out for 45 min at 25° C. and a solution stirring speed of 10 rpm. A titanium dioxide layer is grown in situ on the surface of the titanium foil. After the titanium foil is taken out, the surface is thoroughly cleaned with deionized water and dried.

[0043] (3) Ba(OH)2·8H2O powder was dissolved in deionized water that had been boiled for 10 min to prepare a 2 mol / L barium hydroxide aqueous solution, which was poured into the polytetrafluoroethylene liner of a hydrothermal reactor. The anodized titanium foil in step (2) was placed in the polytetrafluoroethylene liner. The reactor was sealed and placed in an oven at 200°C for 4 days to form a barium titanate layer on the surface of the titanium foil. After the sample was taken out, the surface of the sample was rinsed with 10% by volume acetic acid and deionized water, respectively, and then dried.

[0044] (4) The polyvinylidene fluoride (PVDF) powder was dissolved in N,N-dimethylformamide (DMF) with sufficient stirring to prepare a 1 g / L PVDF casting solution. The casting solution was poured onto the surface of the single-sided barium titanate-treated titanium foil obtained in step (3) using a syringe. The sample was first placed in a vacuum drying oven and kept warm at 70°C for 2 h, and then transferred to an oven and kept warm at 130°C for 10 h to allow the PVDF solution to evaporate the solvent and fully crystallize.

[0045] (5) The P(VDF-TrFE) / BaTiO3 sample was polarized by using a corona polarization device. The P(VDF-TrFE) / BaTiO3 sample obtained in step (4) was tightly attached to the surface of the sample stage. The distance between the needle tip and the sample surface was 5 mm. The voltage of the high-voltage DC power supply was set to 10 kV. There was obvious corona discharge at the needle tip. After 30 minutes of polarization treatment, a P(VDF-TrFE) / BaTiO3 sample with residual polarization was obtained.

[0046] Through the above-mentioned steps, a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure can be prepared in situ on the surface of TA1 titanium foil. The microscopic morphology of the sample cross section under a scanning electron microscope shows that the P(VDF-TrFE) / BaTiO3 piezoelectric composite film has an obvious layered interlocking structure. The lower layer is a relatively dense barium titanate layer, the middle layer is a transition layer of interlocking barium titanate particles and PVDF, and the upper layer is a pure PVDF layer ( Figure 1 ).

[0047] Figure 2 The quasi-static piezoelectric coefficient d 33 The piezoelectric coefficient of the film measured by the measuring instrument, among which the sample of Example 1 after 4 days of hydrothermal time has the highest piezoelectric coefficient d 33 , the value is -271pC / N. The results show that the flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with layer-by-layer interlocking structure exhibits excellent piezoelectric properties.

[0048] Figure 3The ferroelectric loop was obtained by testing the P(VDF-TrFE) / BaTiO3 piezoelectric composite film using a ferroelectric tester. The result shows that the film sample has a high spontaneous polarization characteristic. The film exhibits a low coercive electric field and high residual polarization, indicating that the prepared sample can maintain good piezoelectric properties.

[0049] The schematic diagram of the P(VDF-TrFE) / BaTiO3 device assembled in Example 1 is shown in Figure 4 As shown in the left figure, it includes a top encapsulation PI layer 1, a top conductive silver paste electrode 2, a P(VDF-TrFE) / BaTiO3 piezoelectric film layer 3, a bottom titanium substrate electrode 4 and a bottom encapsulation PI layer 5.

[0050] Figure 4 The figure on the right is a schematic diagram of the device composed of P(VDF-TrFE) / BaTiO3 piezoelectric composite film and the piezoelectric open circuit voltage output curve obtained by bending deformation. The results show that the film sample has good piezoelectric output performance.

[0051] Example 2

[0052] This embodiment provides a method for in-situ generating a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure on the surface of a titanium foil. The steps are basically the same as those in Example 1, with the only difference being that in this experimental example, the hydrothermal reaction time of the anodized titanium foil in step (3) is adjusted to 5 days.

[0053] The P(VDF-TrFE) / BaTiO3 piezoelectric film prepared in this example was measured by a quasi-static piezoelectric coefficient measuring instrument. 33 The value is -274pC / N (the d 33 The value is -271pC / N). Compared with Example 1, extending the hydrothermal time does not significantly improve the piezoelectric coefficient.

[0054] Example 3

[0055] This embodiment provides a method for in-situ generating a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure on the surface of a titanium foil. The steps are basically the same as those in Example 1, with the only difference being that in this experimental example, the hydrothermal reaction time of the anodized titanium foil in step (3) is adjusted to 3 days.

[0056] The P(VDF-TrFE) / BaTiO3 piezoelectric composite film prepared in this example was measured by a quasi-static piezoelectric coefficient measuring instrument. 33 The value is -204pC / N (the d 33The value is -271pC / N). Compared with Example 1, the hydrothermal time is shortened, the barium titanate content and crystallinity are reduced, and the piezoelectric performance of the film is weakened.

[0057] Example 4

[0058] This embodiment provides a method for in-situ generating a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure on the surface of a titanium foil. The steps are basically the same as those in Example 1, with the only difference being that in this embodiment, the hydrothermal reaction time of the anodized titanium foil in step (3) is adjusted to 2 days.

[0059] The P(VDF-TrFE) / BaTiO3 piezoelectric composite film prepared in this example was measured by a quasi-static piezoelectric coefficient measuring instrument. 33 The value is -131pC / N (the d 33 The value is -271pC / N). Compared with Example 1, the barium titanate content and crystallinity are reduced, and the piezoelectric performance of the film is weakened.

[0060] Example 5

[0061] This embodiment provides a method for in-situ generating a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure on the surface of a titanium foil. The steps are basically the same as those in Example 1, with the only difference being that in this experimental example, the hydrothermal reaction time of the anodized titanium foil in step (3) is adjusted to 1 day.

[0062] The P(VDF-TrFE) / BaTiO3 piezoelectric film prepared in this example was measured by a quasi-static piezoelectric coefficient measuring instrument. 33 The value is -45pC / N (the d 33 The value is -271pC / N). Compared with Example 1, the hydrothermal reaction is insufficient, and the content of the crystalline barium titanate phase that can provide a higher piezoelectric response is small, and the piezoelectric performance of the film is weakened.

[0063] Comparative Example 1

[0064] The preparation method of this comparative example is basically the same as that of Example 1, and the same PVDF film forming process as step (4) in Example 1 is adopted to obtain a single P (VDF-TrFE) piezoelectric film, and the P (VDF-TrFE) piezoelectric film is polarized using the same corona polarization device and polarization parameters as in step (5) of Example 1. The only difference is that steps (2)-(3) are omitted.

[0065] The P(VDF-TrFE) piezoelectric film prepared in this comparative example was measured by a quasi-static piezoelectric coefficient measuring instrument. 33The value is -27pC / N (the d 33 The value is -271pC / N). Compared with Example 1, the piezoelectric coefficient of the single P(VDF-TrFE) piezoelectric film without the barium titanate layer is lower. Therefore, the barium titanate piezoelectric layer is in situ generated on the titanium foil surface by anodizing and hydrothermal treatment, and then the P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure is prepared by solution casting process, which can significantly improve the piezoelectric properties of the piezoelectric film.

[0066] Comparative Example 2

[0067] In this comparative example, a barium titanate piezoelectric film is prepared on the surface of a titanium foil only by anodization hydrothermal transformation. The same anodization process as steps (1) and (2) in Example 1 and the same hydrothermal process as in step (3) are used to obtain a barium titanate piezoelectric film on the surface of the titanium foil. The film is polarized using the same corona polarization device and polarization parameters as in step (5) in Example 1.

[0068] The barium titanate piezoelectric film prepared in this comparative example was measured by a quasi-static piezoelectric coefficient measuring instrument. 33 The value is -56pC / N (the d 33 The value is -271pC / N). Compared with Example 1, the barium titanate film without the surface solution-cast P(VDF-TrFE) coating does not have a layer-by-layer interlocking structure, and its piezoelectric coefficient is lower than that of the P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure. Therefore, the preparation of a P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure can significantly improve its piezoelectric properties.

[0069] Comparative Example 3

[0070] The preparation method of this comparative example is basically the same as that of Example 1, except that the electrolyte in step (2) is replaced by a water solvent system electrolyte to perform micro-arc oxidation on the TA1 titanium foil, and the electrolyte is prepared by mixing 0.014 mol / L sodium silicate nonahydrate and 0.017 mol / L sodium hexametaphosphate.

[0071] Figure 5 The typical surface and cross-sectional morphology of the anodized layer of Example 1. Example 1 is anodized TA1 titanium foil in an ethylene glycol organic solvent electrolyte system. The anodized titanium dioxide amorphous layer has a nanocolumn array structure, the nanopores are not interconnected and the sizes are uniformly distributed, and after hydrothermal treatment, a coating with a gradually transitional structure and composition is formed (see Figure 1In comparative example 3, a water-solvent electrolyte system was used to perform micro-arc oxidation on TA1 titanium foil. The prepared micro-arc oxidation coating was a rough and porous ceramic oxide layer with an irregular pore structure and a micron-sized pore. The coating phase structure was mainly composed of an amorphous phase containing Si and P and a titanium dioxide crystalline phase. The amorphous structure also contained amorphous titanium dioxide in the form of (e.g. Figure 6 As shown), the relative content of barium titanate crystals after hydrothermal treatment is low, and barium titanate has no transition region in structure and composition, which is significantly different from the microstructure and phase composition of Example 1.

[0072] The barium titanate prepared in Comparative Example 3 has a low content in the coating and no component transition. The d 33 The value is only the piezoelectric coefficient d of PVDF 33 About -26pC / N (see Figure 2 ), the barium titanate in the coating has no effect on improving the macroscopic piezoelectric properties of the coating. The barium titanate prepared in Example 1 transitions from dense to loose layer by layer, and the surface of the coating is completely barium titanate after hydrothermal treatment. 33 The value is as high as -271pC / N. The difference in the content and structure of barium titanate leads to obvious differences in the piezoelectric properties between Comparative Example 3 and Example 1.

[0073] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film with a layer-by-layer interlocking structure, characterized in that: The following steps are involved: S1. Electrochemically anodic oxidation is performed on titanium foil in an organic electrolyte to generate a TiO2 layer on the surface in situ; wherein the anode is titanium foil and the cathode is an inert conductive electrode; S2, placing the titanium foil treated in step S1 into a barium-containing solution to perform a hydrothermal reaction to in-situ generate a BaTiO3 layer on the surface; S3, coating the P(VDF-TrFE) solution on the surface of the BaTiO3 layer, and annealing to form a flexible P(VDF-TrFE) / BaTiO3 composite film; S4. Performing an electric polarization treatment on the flexible P (VDF-TrFE) / BaTiO3 composite film to obtain the flexible P (VDF-TrFE) / BaTiO3 piezoelectric composite film.

2. The preparation method according to claim 1, characterized in that: In step S1, the titanium foil is a foil of pure titanium or titanium alloy, and has a thickness of 20 to 100 μm.

3. The preparation method according to claim 1, characterized in that: In step S1, the organic electrolyte includes 0.01-0.3 mol / L ammonium fluoride and 0.1-3 mol / L ethylene glycol.

4. The preparation method according to claim 1, characterized in that: In step S1, the parameters of the electrochemical anodization are set as follows: the water bath temperature is 20-30°C, the stirring speed is 5-25rpm, the DC power supply adopts a constant voltage mode, the voltage is 40-80V, and the processing time is 30-90min; the inert conductive electrode includes any one of a graphite electrode, a platinum electrode, and a pure titanium electrode.

5. The preparation method according to claim 1, characterized in that: In step S2, the barium-containing solution includes an aqueous solution of barium hydroxide with a concentration of 1 to 2 mol / L.

6. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 180-220° C., and the reaction time is 1-5 days.

7. The preparation method according to claim 1, characterized in that: In step S3, the concentration of the P(VDF-TrFE) solution is 0.5-3 g / L.

8. The preparation method according to claim 1, characterized in that: In step S3, the annealing treatment is divided into two stages, the first stage is vacuum insulation at 60-80°C for 1-4 hours, and the second stage is insulation at 120-140°C for 6-12 hours.

9. The preparation method according to claim 1, characterized in that: In step S4, the parameters of the polarization treatment are set as follows: the distance between the needle tip and the sample surface is controlled to be between 5 and 20 mm, the high-voltage DC power supply display voltage is adjusted to 5 to 20 kV, and the polarization time is 30 to 90 min.

10. A flexible P(VDF-TrFE) / BaTiO3 piezoelectric composite film having a layer-by-layer interlocking structure obtained by the preparation method as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for growing barium strontium titanate ferroelectric film on surface of titanium substrate in situ, and microarc oxidation electrolyte

    CN105937047A

  • Flexible composite film nano-generator and preparation method thereof

    CN111081863A

  • Self-assembled super-flexible piezoelectric sensor and preparation method and application thereof

    CN114464727A

  • Piezoelectric buffer composite coating and preparation method thereof

    CN117462757A

  • Composite nanofiber membrane, preparation method thereof and flexible piezoelectric device

    CN119041097A